Odpowiedzi

2010-04-14T20:46:03+02:00
1/2(x-6)=x+2/5
1/2x - 3 = x + 2/5
-1/2 x = 3 2/5 / × (-2)
x = 6 4/5

10*1/2/(x-6)=10*x+2/5
5: (x-6) = 10x + 2/5
5/x - 5/6 = 10x + 2/5
5/x + 10 x= 25/30 + 12/30
5/x + 10x = 1 7/30

5(x6)=2*(x+2)
30x = 2x + 4
28x = 4 / : 28
x = 0,142857
1 4 1
2010-04-14T20:48:06+02:00
1/2(x-6)=x+2/5
1/2x-3=x+2/5
1/2x-x=2/5+3
-1/2x=3 2/5/:-1/2
x=-6 4/5

10*1/2/(x-6)=10*x+2/5
5/x-5/6=10x+2/5
5x-5/6=10x+2/5
5x-10x=2/5+5/6
-5x=1 7/30/:-5
x=-0,2

5(x6)=2*(x+2)
30x=2x+4
30x-2x=4
28x=4/:28
x=0,1
1 5 1